Hubungan Lingkungan Fisik Rumah Dengan Penyakit Tuberkulosis Paru Di Puskesmas Kuala Tungkal II, Jambi - Dwi Ruth Rahayuning Asih Budi; Khoidar Amirus; Agung Aji Perdana (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
The purpose of this study was to determine the relationship between occupancy, ventilation area, humidity, temperature, lighting, and floor conditions on pulmonary tuberculosis. This was a case-control study with the number of samples as many 60 cases of positive pulmonary tuberculosis patients and 60 control, not pulmonary tuberculosis patients and applied logistic regression analysis. The result of the bivariate analysis was showing that there was a correlation between pulmonary tuberculosis disease with the physical house condition crowded household, ventilation, room temperature, humidity of the house, lighting, and floor condition p-value indicates a row of ((0.002, 0.028, 0.010, 0.006, 0.003, 0.009). Results of regression analysis showed that ventilation is the most dominant factor affecting pulmonary tuberculosis disease OR (2,207). The conclusion of this study, there is relationship between crowded household, ventilation, room temperature, humidity, light intensity and floor condition with Pulmonary Tuberculosis. Recommended to pay attention to healthly house sanitary aspects in terms of crowded household, ventilation, room temperature, light intensity, floor condition, habit of opening the windows in the morning and increase hygiene and healthy behaviors to prevent transmission of pulmonary tuberculosis and doing health promotion for the community.